Lipid nanoparticle-assisted miR29a delivery based on core-shell nanofibers improves tendon healing by cross-regulation of the immune response and matrix remodeling. (December 2022) - Chen, Wei; Chen, Yi; Ren, Yiming; Gao, Cangjian; Ning, Chao; Deng, Haotian; Li, Peiqi; Ma, Yang; Li, Hao; Fu, Liwei; Tian, Guangzhao; Yang, Zhen; et al.
Abstract: Inferior healing and peritendinous adhesions are the major clinical problems following Achilles tendon injury, leading to impaired motor function and an increased risk of re-rupture. These complications are presumed to be inextricably linked to inflammation and fibroscar formation. Here, microRNA29a is identified as a promising therapeutic target for tendon injury through the cross-regulation of the immune response and matrix remodeling. MiR29a-LNPs were successfully prepared by microfluidic technology. They are then loaded into the core-shell nanofibers to achieve local delivery in the injured tendon, where the shell layer is composed of PELA for anti-adhesion. Our studies reveal that miR29a regulates collagen synthesis and NF-κB activation in tenocytes, and promotes macrophage polarization by inhibiting the inflammasome pathway. In vivo studies of the Achilles tendon-rupture model indicate the best repair in the miR29a group, as evidenced by superior collagen composition and alignment, higher mechanical strength, and better functional recovery. In conclusion, a functionalized anti-adhesive membrane that promotes nascent tendon matrix remodeling and improves the regenerative immune microenvironment is developed for the treatment of tendon injury. Graphical abstract: Image 1